Project Report on 3D Medical Image Information System - VISHAL J, AMIR ALI, LAKSHMISHA and SAILENDRA R (2010)
INTERNAL GUIDE: SUBHAS. SENIOR LECT MVJCE EXTERNAL GUIDE
Keywords: 3D Medical Image Information System